English Learning Activities in Heavy Equipment Engineering Study Program at Olat Maras Community Academy - Musmulyadin, Musmulyadin; Pipit Puspitasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Language learning activities are carried out by language educators so that students gain appropriate language skills after being involved in a learning experience. The essence of learning English in the Heavy Equipment Engineering Study Program at the Olat Maras Community Academy is not only focused on delivering the material contained in the semester learning plan but also on paying attention to creative aspects, student passion for learning, and paying attention to the needs of students humanely and democratically. The lack of learning experience for students, in general, is not only triggered by the difficulty of the content of the subject matter that cannot be understood by students but is also driven by a teaching approach to a learning activity that creates a little learning experience for students during learning. Creating a learning atmosphere full of student activity must involve cognitive, affective, and psychographic students, such as inviting students to listen, practice, argue, and use learning media that originates from the ideas of the students themselves following their study program.